2017
DOI: 10.1002/bip.23084
|View full text |Cite
|
Sign up to set email alerts
|

β‐cyclodextrin encapsulated polyphenols as effective antioxidants

Abstract: Formation of dityrosine (DT) cross-linkages in proteins is one of the most widely used markers of oxidative stress. Ribonuclease A (RNase A) has 6 Tyr residues and shows a characteristic DT fluorescence peak upon oxidation in addition to major changes in its secondary structure. DT formation can be prevented by using polyphenols (GA, ECG, and EGCG) which are known to have strong antioxidant activity. However, it has been observed that ECG and EGCG initiate protein oligomerization due to protein-polyphenol cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Figure 5 shows the effects of GSE on DPPH radical scavenging activity, which were ordered HP-β-CD/GSE (1:2) > HP-β-CD/GSE (1:1) > HP-β-CD/GSE (1:0.5) > GSE. This could be because catechins of the inclusion polyphenol and the two hydroxyl groups at the rim of β-CD engage in hydrogen bonding interactions, and the OH groups in the β-CD wall may be shielded by catechins, which stabilises them and makes them more resistant to oxidation [23]. The result was consistent with that of a previous study [37] in which the antioxidant activity of the rosmarinic acid (RA):HP-β-CD freeze-dried complex was higher than that of RA.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows the effects of GSE on DPPH radical scavenging activity, which were ordered HP-β-CD/GSE (1:2) > HP-β-CD/GSE (1:1) > HP-β-CD/GSE (1:0.5) > GSE. This could be because catechins of the inclusion polyphenol and the two hydroxyl groups at the rim of β-CD engage in hydrogen bonding interactions, and the OH groups in the β-CD wall may be shielded by catechins, which stabilises them and makes them more resistant to oxidation [23]. The result was consistent with that of a previous study [37] in which the antioxidant activity of the rosmarinic acid (RA):HP-β-CD freeze-dried complex was higher than that of RA.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%
“…Researchers have studied various applications of HP-β-CD, including encapsulation of polyphenols [1,21,22]. For example, polyphenol-cyclodextrin inclusion complexes not only prevent dityrosine cross-linkage, but also reduce protein oligomerisation [23], and they can reduce the partial degradation of essential amino acids, thereby decreasing adverse interactions between proteins and polyphenols [24]. Thus, the naturally unstable antioxidant improves antioxidant effects and bioavailability through inclusion.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17]21,38,39 Tea catechins, including EGCG, GCG, ECG, EGC, EC, and GA, have been shown to form stable inclusion complexes with the encapsulating material b-CD, which are demonstrated by using different techniques and theoretical approaches. [15][16][17]21,22,[38][39][40] Despite this, data on the intrinsic molecular interactions of b-CD with these tea catechins assessed using novel biomolecular interaction technology are still relatively limited. In addition, tea catechins, especially EGCG, are easily oxidized and unstable at high pH or on prolonged exposure to high temperature.…”
Section: Bli Studiesmentioning
confidence: 99%
“…17 In addition, extensive experiments have been performed to illuminate the interactions between individual catechins and b-CD using a number of techniques. 7,[15][16][17][20][21][22] Based on the distinctive characteristics of b-CD, it has also been successfully used to extract EGCG and ECG from tea leaves. 23,24 However, to the best of our knowledge, fundamental data on the real-time interactions between b-CD and EGCG, ECG, EGC and EC are still relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, hydroxypropyl‐β‐cyclodextrin (HP‐β‐CD) as a derivative of β‐CD has gained increasing attention due to its low toxicity, improved aqueous solubility, and flexible cavity (Dreassi et al., 2010; Liu et al., 2013; Tang et al., 2016). Previous studies found that polyphenols have high activity in cyclodextrin, thereby inhibiting polyphenol‐induced protein aggregation (Budryn, Zaczyńska, Rachwa‐Rosiak, & Oracz, 2015; Niccoli, Oliva, & Castronuovo, 2017; Roy, Dinda, Chaudhury, & Dasgupta, 2017). Therefore, the above research inspires the testing of HP‐β‐CD to improve the loading capacity of TP due to the interference of protein–polyphenol interaction.…”
Section: Introductionmentioning
confidence: 99%